The Dynamics of Legal Politics in Indonesia’s Democratic System: Power Configuration and Legislative Formation - Sudirman Samual; Basman; Ronal Regen; Elnymartin; Erwin; Lukman (Pustaka Digital Indonesia, 2026)
Legal politics constitutes the strategic direction through which the state formulates, implements, and develops legal norms in accordance with constitutional objectives and democratic values. In Indonesia's democratic system, legislative formation is shaped by complex interactions among political institutions, public participation, constitutional principles, and competing power configurations. This study aims to analyze the dynamics of legal politics in Indonesia and examine how political power influences the legislative process within a constitutional democracy. The research employs a normative legal method complemented by a qualitative approach, utilizing statutory, conceptual, and historical analyses of legislation, constitutional doctrines, judicial decisions, and relevant scholarly literature. The findings indicate that legal politics in Indonesia is highly dynamic, reflecting shifting balances of power between the executive, legislature, judiciary, political parties, and civil society. Although democratization has strengthened constitutional oversight and expanded opportunities for public participation, legislative outcomes remain vulnerable to elite bargaining, partisan interests, and political intervention, which may undermine legal certainty, justice, and regulatory coherence. Furthermore, the study demonstrates that constitutional review, institutional checks and balances, and meaningful civic engagement play essential roles in preserving democratic accountability and limiting the politicization of lawmaking. It concludes that effective legal politics requires transparent legislative procedures, independent legal institutions, evidence-based policymaking, and sustained public participation to ensure that legislation reflects constitutional values rather than short-term political interests. Strengthening these democratic mechanisms is essential for promoting responsive governance, legal legitimacy, and sustainable constitutional development in Indonesia.